2007
DOI: 10.1302/0301-620x.89b9.19339
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cruciate ligament reconstruction using autologous double hamstrings: a comparison of standard versus minimal debridement techniques using MRI to assess revascularisation

Abstract: Animal studies have shown that implanted anterior cruciate ligament (ACL) grafts initially undergo a process of revascularisation prior to remodelling, ultimately increasing mechanical strength. We investigated whether minimal debridement of the intercondylar notch and the residual stump of the ruptured ACL leads to earlier revascularisation in ACL reconstruction in humans. We undertook a randomised controlled clinical trial in which 49 patients underwent ACL reconstruction using autologous four-strand hamstri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
194
1
13

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(210 citation statements)
references
References 22 publications
2
194
1
13
Order By: Relevance
“…6 Matsumoto et al 7 noted that the area around the ACL septum contains a population of vascular-derived stem cells that may contribute to ligament regeneration and repair at the rupture site. In a canine model, they elucidated that transplantation of ACL-ruptured tissue contributed to early tendon-bone healing.…”
Section: Discussionmentioning
confidence: 99%
“…6 Matsumoto et al 7 noted that the area around the ACL septum contains a population of vascular-derived stem cells that may contribute to ligament regeneration and repair at the rupture site. In a canine model, they elucidated that transplantation of ACL-ruptured tissue contributed to early tendon-bone healing.…”
Section: Discussionmentioning
confidence: 99%
“…3 Gohil et al 13 reported a 59% incidence of cyclops formation after ACL reconstruction with minimal debridement of the notch tissue compared with 37.5% in patients with standard debridement (although the difference did not reach statistical significance). However, the flap of soft tissue that we have described lies posterosuperior to the proximal part of the graft; thus it cannot cause any impingement.…”
Section: Discussionmentioning
confidence: 98%
“…3,13 In our technique, we elevate the available thin layer of tissue including the remnant of the ACL with gentle dissection over the femoral condyle, leaving it attached at the back, and then the tunnel or socket is made directly on the bone and not through the soft tissues. On the other hand, on the tibial side, the tunnel is made through the ACL remnant itself.…”
Section: Discussionmentioning
confidence: 99%
“…2 Gohil et al used MRI scans to assess differences in revascularization after the use of standard vs minimal debridement techniques. 23 They indicated that minimal debridement leads to earlier revascularization within the midsubstance of the ACL graft at two months. There was a significant reduction of the mid-substance signal six months after use of the minimal debridement technique.…”
Section: S76mentioning
confidence: 99%